2016
DOI: 10.3917/lig.802.0032
|View full text |Cite
|
Sign up to set email alerts
|

Mens sana in corpore turistico  : le corps « dé-routinisé » au prisme des pratiques touristiques

Abstract: Le tourisme en tant que pratique à dimension spatiale, suppose une mise à distance des lieux du quotidien. Nous questionnons ici cette discontinuité à travers le concept de « dé-routinisation » proposé par Norbert Elias. Ce dernier permet en effet de comprendre les manières dont le corps des touristes est engagé dans la pratique des lieux autres, à partir du moment où les individus y mettent à l'épreuve leurs routines. C'est ce que nous appelons, par construction d'idéaux types, les quatre corps du touriste : … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This coastal population shares both a language, Kiswahili, and a religion, Islam (Le Guennec-Coppens, 2002;Sheriff, 2010). 3 Following Norbert Elias, some authors have shown that the "de-routinization" that characterizes the tourism experience involves a relaxation of daily constraints, thereby influencing the bodily and emotional behavior of tourists (Coëffé et al 2016;Selänniemi, 2003). For a sociohistory of bodily practices during the summer (in a Western context), see also Granger 2017.…”
Section: Aknowledgmentsmentioning
confidence: 99%
“…This coastal population shares both a language, Kiswahili, and a religion, Islam (Le Guennec-Coppens, 2002;Sheriff, 2010). 3 Following Norbert Elias, some authors have shown that the "de-routinization" that characterizes the tourism experience involves a relaxation of daily constraints, thereby influencing the bodily and emotional behavior of tourists (Coëffé et al 2016;Selänniemi, 2003). For a sociohistory of bodily practices during the summer (in a Western context), see also Granger 2017.…”
Section: Aknowledgmentsmentioning
confidence: 99%